Mycolactone cytotoxicity in Schwann cells could explain nerve damage in Buruli ulcer. - Junichiro En; Sho Kitamoto; Akira Kawashima; Suguru Yonezawa; Yoshito Kishi; Norihisa Ishii; Masamichi Goto (Public Library of Science (PLoS), 2017)
Buruli ulcer is a chronic painless skin disease caused by Mycobacterium ulcerans. The local nerve damage induced by M. ulcerans invasion is similar to the nerve damage evoked by the injection of mycolactone in a Buruli ulcer mouse model. In order to elucidate the mechanism of this nerve damage, we tested and compared the cytotoxic effect of synthetic mycolactone A/B on cultured Schwann cells, fibroblasts and macrophages. Mycolactone induced much higher cell death and apoptosis in Schwann cell line SW10 than in fibroblast line L929. These results suggest that mycolactone is a key substance in the production of nerve damage of Buruli ulcer.